Catastrophic health expenditure of households with hypertension: a comparative study in China - Zhai, Xiaohui; Zhou, Zhongliang; Liu, Guanping; Lu, Jiao; Zhao, Yaxin; Cao, Dan; Zhao, Dantong; Lai, Sha; Fan, Xiaojing (Frontiers in Public Health, 2023)
Objectives: The aim of this study was to understand the impact of multimorbidity on catastrophic health expenditures for people with hypertension. Methods: Data were obtained from the China Health and Retirement Longitudinal Study (CHARLS) in 2018, 8342 adults were included in our analysis. Propensity score matching method was used to compare the risk of CHE between the hypertension patients (treatment group) and those without any chronic disease (control group) in middle-aged and elderly people. Patients with hypertension were also divided into two groups: only hypertension and multimorbidity. Results: Hypertension increased the likelihood of CHE by 11.3% in older adults. Further analysis showed that hypertension alone does not increase the risk of CHE, and the risk of CHE in hypertension patients with multimorbidity was 12.9% higher than those without chronic disease. Conclusions: Our study highlights the importance of healthy management of patients with only hypertension and preventing them from developing multimorbidity.